Pengaruh Temperatur terhadap Mekanisme Inhibisi oleh Sistein pada Korosi Baja Karbon dalam Larutan NaCl Jenuh CO2 - Yayan Sunarya; Cynthia Linaya Radiman; Sadijah Achmad; Bunbun Bundjali (Jurnal Matematika & Sains, 2008)
The inhibition mechanism of cysteine on API 5L X65 carbon steel corrosion in CO2-saturated NaCl solution at 300K â360K was studied. The investigations involved potentiodynamic polarization, electrochemical impedance spectroscopy(EIS) methods and computer simulation of Zview program. The results showed that the inhibition mechanism takes placethrough formation of passive layers that covers carbon steel surface with inhibition efficiency up to 85%. Functionalgroup dominantly involved in the formation process of the passive layers is âSH at low temperature, and âNH3+ athigh temperature. The increasing temperature alters the carbon steel corrosion/inhibition process from kinetics ofcharge transfer to diffusion process.